T-shirt Illustration for Griya Baca's Street Children as an Awareness Campaign Media - Gunawan, Indra; Verdiana, Elfa Olivia (VCD: Journal of Visual Communication Design, 2023)
Street children are a social problem that is an interesting phenomenon in social life. Quoting from street children who are cared for by Griya Baca Malang, here there are a lot of children who do not get an education like ordinary children, due to their circumstances which require them to live on the streets, even earn money by busking/begging, their background is mostly from economic pressure. , from this problem it is important for the community to care more about them because after all they are the nation's generation, after research on the problem, the solution for this is to hold a awareness campaign through t-shirt illustrations. The purpose of designing this t-shirt illustration is as a form of public awareness to be more concerned with street children. Illustrations will make it easier to convey messages and have their own charm so that messages from the campaign can be conveyed properly. Product effectiveness testing was carried out on February 16, 2022, showing that the results of the assessment of this t-shirt illustration obtained a fairly high positive percentage, namely 29 out of 30 respondents. This book received a positive response from respondents based on the results obtained from this test. Keywords: Street children, illustration, campaign